qanda-logo
search-icon
Symbol
apple-logo
google-play-logo

Calculator search results

Formula
Solve the quadratic equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
Number of solution
Answer
circle-check-icon
Relationship between roots and coefficients
Answer
circle-check-icon
Graph
$y = x ^ { 2 } + 2 x + 4$
$y = 0$
$y$Intercept
$\left ( 0 , 4 \right )$
Minimum
$\left ( - 1 , 3 \right )$
Standard form
$y = \left ( x + 1 \right ) ^ { 2 } + 3$
$x ^{ 2 } +2x+4 = 0$
$\begin{array} {l} x = - 1 + \sqrt{ 3 } i \\ x = - 1 - \sqrt{ 3 } i \end{array}$
Solve quadratic equations using the square root
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 4 } = \color{#FF6800}{ 0 }$
$ $ Convert the quadratic expression on the left side to a perfect square format $ $
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 4 } \color{#FF6800}{ - } \color{#FF6800}{ 1 } ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 0 }$
$\left ( x + 1 \right ) ^ { 2 } \color{#FF6800}{ + } \color{#FF6800}{ 4 } \color{#FF6800}{ - } \color{#FF6800}{ 1 } ^ { \color{#FF6800}{ 2 } } = 0$
$ $ Move the constant to the right side and change the sign $ $
$\left ( x + 1 \right ) ^ { 2 } = \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ + } \color{#FF6800}{ 1 } ^ { \color{#FF6800}{ 2 } }$
$\left ( x + 1 \right ) ^ { 2 } = - 4 + \color{#FF6800}{ 1 } ^ { \color{#FF6800}{ 2 } }$
$ $ Calculate power $ $
$\left ( x + 1 \right ) ^ { 2 } = - 4 + \color{#FF6800}{ 1 }$
$\left ( x + 1 \right ) ^ { 2 } = \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ + } \color{#FF6800}{ 1 }$
$ $ Add $ - 4 $ and $ 1$
$\left ( x + 1 \right ) ^ { 2 } = \color{#FF6800}{ - } \color{#FF6800}{ 3 }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ - } \color{#FF6800}{ 3 }$
$ $ Solve quadratic equations using the square root $ $
$\color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \pm \sqrt{ \color{#FF6800}{ - } \color{#FF6800}{ 3 } }$
$\color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \pm \sqrt{ \color{#FF6800}{ - } \color{#FF6800}{ 3 } }$
$ $ Solve a solution to $ x$
$\color{#FF6800}{ x } = \pm \sqrt{ \color{#FF6800}{ 3 } } \color{#FF6800}{ i } \color{#FF6800}{ - } \color{#FF6800}{ 1 }$
$\color{#FF6800}{ x } = \pm \sqrt{ \color{#FF6800}{ 3 } } \color{#FF6800}{ i } \color{#FF6800}{ - } \color{#FF6800}{ 1 }$
$ $ Separate the answer $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ + } \sqrt{ \color{#FF6800}{ 3 } } \color{#FF6800}{ i } \\ \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ - } \sqrt{ \color{#FF6800}{ 3 } } \color{#FF6800}{ i } \end{array}$
$\begin{array} {l} x = - 1 + \sqrt{ 3 } i \\ x = - 1 - \sqrt{ 3 } i \end{array}$
Calculate using the quodratic formula$($Imaginary root solution$)
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 4 } = \color{#FF6800}{ 0 }$
$ $ Solve the quadratic equation $ ax^{2}+bx+c=0 $ using the quadratic formula $ \dfrac{-b\pm\sqrt{b^{2}-4ac}}{2a}$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 2 \pm \sqrt{ 2 ^ { 2 } - 4 \times 1 \times 4 } } { 2 \times 1 } }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 2 \pm \sqrt{ 2 ^ { 2 } - 4 \times 1 \times 4 } } { 2 \times 1 } }$
$ $ Organize the expression $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 2 \pm \sqrt{ - 12 } } { 2 \times 1 } }$
$x = \dfrac { - 2 \pm \sqrt{ \color{#FF6800}{ - } \color{#FF6800}{ 12 } } } { 2 \times 1 }$
$ $ Organize the part that can be taken out of the radical sign inside the square root symbol $ $
$x = \dfrac { - 2 \pm \color{#FF6800}{ 2 } \sqrt{ \color{#FF6800}{ 3 } } \color{#FF6800}{ i } } { 2 \times 1 }$
$x = \dfrac { - 2 \pm 2 \sqrt{ 3 } i } { 2 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } }$
$ $ Multiplying any number by 1 does not change the value $ $
$x = \dfrac { - 2 \pm 2 \sqrt{ 3 } i } { \color{#FF6800}{ 2 } }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 2 \pm 2 \sqrt{ 3 } i } { 2 } }$
$ $ Separate the answer $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 2 + 2 \sqrt{ 3 } i } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 2 - 2 \sqrt{ 3 } i } { 2 } } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { - 2 + 2 \sqrt{ 3 } i } { 2 } } \\ x = \dfrac { - 2 - 2 \sqrt{ 3 } i } { 2 } \end{array}$
$ $ Reduce the fraction $ $
$\begin{array} {l} x = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ + } \sqrt{ \color{#FF6800}{ 3 } } \color{#FF6800}{ i } \\ x = \dfrac { - 2 - 2 \sqrt{ 3 } i } { 2 } \end{array}$
$\begin{array} {l} x = - 1 + \sqrt{ 3 } i \\ x = \color{#FF6800}{ \dfrac { - 2 - 2 \sqrt{ 3 } i } { 2 } } \end{array}$
$ $ Reduce the fraction $ $
$\begin{array} {l} x = - 1 + \sqrt{ 3 } i \\ x = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ - } \sqrt{ \color{#FF6800}{ 3 } } \color{#FF6800}{ i } \end{array}$
$ $ Do not have the solution $ $
Calculate using the quadratic formula
$x = \dfrac { - 2 \pm \sqrt{ \color{#FF6800}{ 2 } ^ { \color{#FF6800}{ 2 } } - 4 \times 1 \times 4 } } { 2 \times 1 }$
$ $ Calculate power $ $
$x = \dfrac { - 2 \pm \sqrt{ \color{#FF6800}{ 4 } - 4 \times 1 \times 4 } } { 2 \times 1 }$
$x = \dfrac { - 2 \pm \sqrt{ 4 - 4 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } \times 4 } } { 2 \times 1 }$
$ $ Multiplying any number by 1 does not change the value $ $
$x = \dfrac { - 2 \pm \sqrt{ 4 - 4 \times 4 } } { 2 \times 1 }$
$x = \dfrac { - 2 \pm \sqrt{ 4 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 4 } } } { 2 \times 1 }$
$ $ Multiply $ - 4 $ and $ 4$
$x = \dfrac { - 2 \pm \sqrt{ 4 \color{#FF6800}{ - } \color{#FF6800}{ 16 } } } { 2 \times 1 }$
$x = \dfrac { - 2 \pm \sqrt{ \color{#FF6800}{ 4 } \color{#FF6800}{ - } \color{#FF6800}{ 16 } } } { 2 \times 1 }$
$ $ Subtract $ 16 $ from $ 4$
$x = \dfrac { - 2 \pm \sqrt{ \color{#FF6800}{ - } \color{#FF6800}{ 12 } } } { 2 \times 1 }$
$x = \dfrac { - 2 \pm \sqrt{ - 12 } } { 2 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } }$
$ $ Multiplying any number by 1 does not change the value $ $
$x = \dfrac { - 2 \pm \sqrt{ - 12 } } { \color{#FF6800}{ 2 } }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 2 \pm \sqrt{ - 12 } } { 2 } }$
$ $ The square root of a negative number does not exist within the set of real numbers $ $
$ $ Do not have the solution $ $
$ $ Do not have the real root $ $
Find the number of solutions
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 4 } = \color{#FF6800}{ 0 }$
$ $ Determine the number of roots using discriminant, $ D=b^{2}-4ac $ from quadratic equation, $ ax^{2}+bx+c=0$
$\color{#FF6800}{ D } = \color{#FF6800}{ 2 } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 1 } \color{#FF6800}{ \times } \color{#FF6800}{ 4 }$
$D = \color{#FF6800}{ 2 } ^ { \color{#FF6800}{ 2 } } - 4 \times 1 \times 4$
$ $ Calculate power $ $
$D = \color{#FF6800}{ 4 } - 4 \times 1 \times 4$
$D = 4 - 4 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } \times 4$
$ $ Multiplying any number by 1 does not change the value $ $
$D = 4 - 4 \times 4$
$D = 4 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 4 }$
$ $ Multiply $ - 4 $ and $ 4$
$D = 4 \color{#FF6800}{ - } \color{#FF6800}{ 16 }$
$D = \color{#FF6800}{ 4 } \color{#FF6800}{ - } \color{#FF6800}{ 16 }$
$ $ Subtract $ 16 $ from $ 4$
$D = \color{#FF6800}{ - } \color{#FF6800}{ 12 }$
$\color{#FF6800}{ D } = \color{#FF6800}{ - } \color{#FF6800}{ 12 }$
$ $ Since $ D<0 $ , there is no real root of the following quadratic equation $ $
$ $ Do not have the real root $ $
$\alpha + \beta = - 2 , \alpha \beta = 4$
Find the sum and product of the two roots of the quadratic equation
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 4 } = \color{#FF6800}{ 0 }$
$ $ In the quadratic equation $ ax^{2}+bx+c=0 $ , if the two roots are $ \alpha, \beta $ , then it is $ \alpha + \beta =-\dfrac{b}{a} $ , $ \alpha\times\beta=\dfrac{c}{a}$
$\color{#FF6800}{ \alpha } \color{#FF6800}{ + } \color{#FF6800}{ \beta } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 2 } { 1 } } , \color{#FF6800}{ \alpha } \color{#FF6800}{ \beta } = \color{#FF6800}{ \dfrac { 4 } { 1 } }$
$\alpha + \beta = - \dfrac { 2 } { \color{#FF6800}{ 1 } } , \alpha \beta = \dfrac { 4 } { 1 }$
$ $ If the denominator is 1, the denominator can be removed $ $
$\alpha + \beta = - \color{#FF6800}{ 2 } , \alpha \beta = \dfrac { 4 } { 1 }$
$\alpha + \beta = - 2 , \alpha \beta = \dfrac { 4 } { \color{#FF6800}{ 1 } }$
$ $ If the denominator is 1, the denominator can be removed $ $
$\alpha + \beta = - 2 , \alpha \beta = \color{#FF6800}{ 4 }$
Solution search results
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple-logo
google-play-logo